Interpretation of positron lifetime spectra via least squares prony method - Kul’ment’ev, A.I. (Вопросы атомной науки и техники, 2013)
A method of numerical analysis of positron annihilation lifetime spectra has been devised. A new approach to determine the number of components in a spectrum was proposed and regularization procedure to solve the inverse problem concerning the estimation of useful components characteristics was formulated. The results obtained for model spectra demonstrate high resolution capability of proposed method. Розроблено метод чисельного аналiзу спектрiв часу життя позитронiв. Запропоновано новий пiдхiд до визначення числа компонент у спектрi i сформульована регуляризацiйна процедура вирiшення зворотної задачi оцiнки характеристик корисних компонент. Результати, якi отриманнi на модельних спектрах, демонструють високу роздiльну здатнiсть запропонованого методу. Разработан метод численного анализ аспектров времени жизни позитронов. Предложен новый подход определения числа компонент в спектре и сформулирована регуляризационная процедура решения обратной задачи оценки характеристик полезных компонент. Результаты, полученные на модельных спектрах, демонстрируют высокую разрешающую способность предложенного метода.